The Difference Of Feed Consumption, Body Weight, And Feed Conversation Ratio Between Male Muscovy Duck (Cairina moschata) And Male Mule Duck At The Growing Age - Restiadi, Tjuk Imam (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2023)
This study aims to collect data on comparisons of the differences in body size between Muscovy Duck and Mule Duck that can be observed from feed consumption, weight gain and feed conversion ratio between Cairina moschata and Mule Duck to find out the best waterfowl as a cut poultry. Cairina moschata and Mule Duck that are maintained at the age of the growth phase that is from the age of 5 weeks to 9 weeks with gender male Cairina moschata and male Mule Duck were used in this study. The number of samples that were used was 10 Cairina moschata and 10 Mule Duck. The results of the data processing of this study used a t test method in SPSS. The results of this study were the consumption of Mule Duck feed is much more than Muscovy Duck, the weight gain of Mule Duck is much more than Muscovy Duck, and Mule Duck have a lower feed conversion ratio compared to the Muscovy Duck. This experiment concluded that Mule Duck performance are more superior compared to Muscovy Duck.